University accommodation online registration : a business model for UiTM Shah Alam Colleges / Mohd Fairus Khaminee Ismail - Ismail, Mohd Fairus Khaminee (2005)
With the advancement of the technology in our world nowadays, online registration has become more and more acceptable in ftdfiU the needs of human. For instance, in applying jobs as well as m educations registration. UiTM itself has provided online registration. The students were asked to register their subject through online registration every semester. This practice is acceptable by UiTM students. The University Accommodation Online Registration (UAOR) is introduced as an alternative way in solving problems that occur in manual registration such as the problem of overlapping students' data and students do not receive college offer letter. Through manual system of registration, student need go to the college office to take the college registration form and the fill it. After that, the students are required to send the form to college office together with envelope that has been written on their address, guardians salary shp and activity card. This tradition should be done every semester. By implementing the system of UAOR, UiTM student can access and do flie online registration for their subject from anywhere and anytime with the duration stated by HEP circular. Other than that, this system also helps HEP to manage the students' data accurately. In a nutshell, the introduction of UAOR will definitely give a new dimension to college online registration.